Pengembangan Model Problem Based Learning Berbasis Kearifan Lokal Untuk Meningkatkan Sikap Sosial Siswa Kelas III Di MI RoudlotusShibyan Beton Menganti Gresik - Nur Rokhimah; Nurul Agustin; Muhammad Luthfi Efendi (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
This study was motivated by the low student engagement in learning and the suboptimal development of social attitudes such as cooperation, responsibility, and communication among third-grade students at MI Roudlotus Shibyan Beton Menganti Gresik. Teacher-centered learning and the lack of integration of local cultural potential were identified as the main research gaps. This study aimed to develop a Problem Based Learning (PBL) model based on local wisdom using the traditional game congklak as a learning medium, to examine the model’s validity, practicality, and effectiveness, and to improve students’ social attitudes. The research employed a Research and Development (R&D) approach with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, questionnaires, tests, and documentation, and analyzed using quantitative descriptive methods. The validation results for the learning tools, materials, media, and student worksheets indicated a “highly feasible” category with percentages above 91%. Students’ responses to the model were categorized as “good” (75.6%), while post-learning social attitude assessments averaged 96% (very good), with the highest scores in cooperation and respect indicators (97.5%). The findings confirm that the PBL model based on local wisdom through congklak media is effective in fostering students’ social character and increasing their engagement in the learning process.